2005
DOI: 10.1002/mds.20668
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of microglial activation with [11C](R)‐PK11195 PET in progressive supranuclear palsy

Abstract: Progressive supranuclear palsy (PSP) is a neurodegenerative disease presenting with voluntary gaze difficulties, early falls, and Parkinsonism. Neuronal loss, associated with intracellular neurofibrillary tangles and activated microglia, is found targeting the basal ganglia, brainstem nuclei, and frontal cortex. [11C](R)-PK11195 PET is a marker of peripheral benzodiazepine binding sites (PBBS) expressed by activated microglia. We have used [11C](R)-PK11195 PET to demonstrate in vivo the degree and distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(120 citation statements)
references
References 17 publications
7
113
0
Order By: Relevance
“…Whereas results of previous PET studies using 11 C-PK11195 in Parkinson's disease showed increased binding in the midbrain 35 and different frontal and temporal cortical regions, 36 other reports did not identify major differences between binding in Parkinson's disease and controls. 37 Conversely, more consistent increases in 11 C-PK11195 binding have been reported in multiple systems atrophy, 38 progressive supranuclear palsy, 39 corticobasal degeneration, 40 and Huntington's disease. 41 Reasons for such variability could include limitations inherent to this particular tracer, such as high non-specific binding, low brainpenetration, high plasma-protein-binding, and difficult preparation.…”
Section: Neuroinflammationmentioning
confidence: 83%
“…Whereas results of previous PET studies using 11 C-PK11195 in Parkinson's disease showed increased binding in the midbrain 35 and different frontal and temporal cortical regions, 36 other reports did not identify major differences between binding in Parkinson's disease and controls. 37 Conversely, more consistent increases in 11 C-PK11195 binding have been reported in multiple systems atrophy, 38 progressive supranuclear palsy, 39 corticobasal degeneration, 40 and Huntington's disease. 41 Reasons for such variability could include limitations inherent to this particular tracer, such as high non-specific binding, low brainpenetration, high plasma-protein-binding, and difficult preparation.…”
Section: Neuroinflammationmentioning
confidence: 83%
“…Microglial activation has been demonstrated in vivo using [ 11 C](R)-PK11195 PET in the brains of patients with idiopathic PD 44,45 and atypical parkinsonism, such as multiple system atrophy, 46 progressive supranuclear palsy, 47 and corticobasalganglionic degeneration. 48 In these conditions, the distribution of [ 11 C](R)-PK11195 binding mirrors the spatial pattern of known distinct neuropathologic hallmarks.…”
Section: Movement Disordersmentioning
confidence: 99%
“…Both [ 11 C](R)-PK11195 and [ 11 C]PK11195 have been used as positron emmision tomography (PET) tracers to study activated microglia in various neurologic disorders. It has been used to study stroke (Ramsay et al, 1992;Pappata et al, 2000;Gerhard et al, 2000Gerhard et al, , 2005a), Alzheimer's disease (Groom et al, 1995; Cagnin et al, 2001a;Versijpt et al, 2003), multiple sclerosis (Banati et al, 2000;Debruyne et al, 2002Debruyne et al, , 2003Versijpt et al, 2005) and various other diseases (Pappata et al, 1991; Banati et al, 1999Banati et al, , 2001Goerres et al, 2001;Cagnin et al, 2001bCagnin et al, , 2004Cicchetti et al, 2002;Gerhard et al, 2003Gerhard et al, , 2004Gerhard et al, , 2005bTurner et al, 2004Turner et al, , 2005Venneti et al, 2004;Henkel et al, 2004;Ouchi et al, 2005). Most studies have used a reference tissue approach to quantify binding, either by applying the simplified reference tissue model (SRTM) (Lammertsma and Hume, 1996) or by using uptake normalized to a reference region.…”
mentioning
confidence: 99%